Access to Healthcare for Cancer Patients in Lithuania During the COVID-19 Pandemic - Petrauskas, Vidas; Narbutas, Šarūnas; Čiakienė, Neringa; Gudelytė, Guoda; Dulskas, Audrius (Acta medica Lituanica, 2021)
Letter to the editor